Changing Characteristics of Sandstone Pore Size under Cyclic Loading. (5th March 2021) - Kan, Jiaguang; Li, Guichen; Zhang, Nong; Wang, Peng; Han, Changliang; Wang, Shun
Abstract : The size and distribution of pores in rocks are closely related to their physical and mechanical properties. It is important to study the structure and distribution of pore size inside the rock to assess the risk of damage to a given rock volume. These characteristics were studied under different pressures, pore diameters, and pore throat size distribution laws using a UTM5540 electronic universal testing machine, magnetic resonance imaging scanning, and low field nuclear magnetic resonance spectroscopy with cyclic loading on yellow sandstone. We found the following. (1) Under 0–10 MPa load, the peaks of the sandstone T 2 spectrum move left as load increases, and the porosity of the sandstone decreases. The peak area of the middle relaxation spectrum increases as pressure increases from 10 to 20 MPa, and a peak for the long relaxation time spectrum appears. (2) Under 0–10 MPa load, the spectral peak associated with a large pore moves left and decreases in area as pressure increases. Under 10–20 MPa load, the large-pore spectral peak moves right and increases in area as pressure increases. (3) Under the applied 0–10 MPa load, the porosity of water-saturated sandstone gradually decreases, and the sandstone NMR images darken with increasing load. The porosity of saturated sandstone gradually increases under 10–20 MPa pressure, and its NMR image brightens. (4) The number of small pore throats increases with increasing load, but the number of large- and medium-sized pore throats decreases. From 0 to 15 MPa, crack (>1 micron) abundance decreases, and fractures are generated by compaction under a 20 MPa load. The pore interconnectivity is enhanced, as are the number and size of pores in the sandstone. With continuing increasing pressure, the numbers of pores and penetration of cracks increase, which damages the sandstone.